Systemic Concentrations of Short Chain Fatty Acids Are Elevated in Salmonellosis and Exacerbation of Familial Mediterranean Fever - Ktsoyan, Zhanna A.; Mkrtchyan, Mkhitar S.; Zakharyan, Magdalina K.; Mnatsakanyan, Armine A.; Arakelova, Karine A.; Gevorgyan, Zaruhi U.; Sedrakyan, Anahit M.; Hovhannisyan, Alvard I.; Arakelyan, Arsen A.; Aminov, Rustam I. (Frontiers in Microbiology, 2016)
Gut microbiota-produced short chain fatty acids (SCFAs) play an important role in the normal human metabolism and physiology. Although the gradients of SCFAs from the large intestine, where they are largely produced, to the peripheral blood as well as the main routes of SCFA metabolism by different organs are known well for the healthy state, there is a paucity of information regarding how these are affected in disease. In particular, how the inflammation caused by infection or autoinflammatory disease affect the concentration of SCFAs in the peripheral venous blood. In this work, we revealed that diseases caused either by infectious agents (two Salmonella enterica serovars, S. Enteritidis and S. Typhimurium) or by the exacerbation of an autoinflammatory disease, familial Mediterranean fever (FMF), both result in a significantly elevated systemic concentration of SCFAs. In the case of salmonellosis the concentration of SCFAs in peripheral blood was significantly and consistently higher, from five- to 20-fold, compared to control. In the case of FMF, however, a significant increase of SCFAs in the peripheral venous blood was detected only in the acute phase of the disease, with a lesser impact in remission. It seems counterintuitive that the dysbiotic conditions, with a reduced number of gut microorganisms, produce such an effect. This phenomenon, however, must be appraised within the context of how the inflammatory diseases affect the normal physiology. We discuss a number of factors that may contribute to the “leak” and persistence of gut-produced SCFAs into the systemic circulation in infectious and autoinflammatory diseases.